Psychological jurisprudence and the working “tools” of justice: Diagnostic commentary and transgressive philosophy - Arrigo, Bruce A. (Punishment & society, 2025)
The practice framework of psychological jurisprudence provides researchers, educators, and policy professionals with a critically animated theory and a humanistically-oriented science by which to diagnose the status of coexistent wellbeing in diverse carceral spaces and settings. These are environs in which the systems of mental health, substance abuse, and offender rehabilitation function to oversee the treatment needs of incarcerated persons and to manage the workplace concerns of care and custody providers. Diagnosing the status of coexistent wellbeing (e.g. reciprocal awareness and insight, inter-subjective knowing and understanding, mutual respect and trust) within these environs is made possible given that everyday symbols, mundane texts, and routine customs populate these spaces and settings. I argue that recognizing and responding to shared wellbeing's status requires a set of “tools.” Reliance on these tools reframes the conversation about personal insight, institutional responsibility, collective change, the public good, and even justice for a people yet-to-be. Accordingly, in this paper, I delineate several core concepts from within the theory and science of psychological jurisprudence that facilitate this reframing. These concepts represent a set of working tools that further the humanistic purpose of this practice framework. To initiate the paper's diagnostic intention, I begin by describing psychological jurisprudence as a philosophy of relationality. This description emphasizes the unique role, relevance, and scope of this philosophy, and it pinpoints why the practice framework of psychological jurisprudence represents an alternative model of correctional treatment that reconceives justice and its ethical administration.